Financial Performance of Malaysian Founder Islamic Banks Versus Conventional Banks - Rosnia Masruki; Norhazlina Ibrahim; Hishamuddin Abdul Wahab; Elmirina Osman (World Business Institute, 2024)
This paper analyses and measures the performance of two Islamic Banks (Bank Islam and Bank Muamalat) as they deemed to be the pioneer and spearhead of the Islamic banking system in Malaysia. Both banks are then benchmarked against the conventional banks' performance over 5 years (2004-2008).When comparing Islamic banks profitability and liquidity against conventional banks, we found that Islamic banks are less profitable but have better liquidity than conventional banks. The higher profitability of conventional banks is due to the higher net financing and better asset quality that they have. In term of credit risk, we found that the conventional banks encountered high credit risk since their LDR much higher than Islamic banks. Future studies should expand this line of study to examine the best strategy that Islamic Banks can implement in order to attract more non-Muslims borrowers to apply financing from Islamic Banks even though Islamic Banks charging higher profit mark-up.